From Compliance to Commodity: Halal Commodification, the Price of Compliance, and Authority Tensions in Indonesia's JPH System - Muhammad Toriq Nurmadiansyah; Muhammad Irfai Muslim (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2026)
This study aims to analyze how Indonesia's Halal Product Assurance System (JPH) transforms halal from a religious consumption norm into a market and legal infrastructure. The analysis focuses on label commodification, the price of compliance, policy acceleration, and authority tensions in the implementation of JPH. This study uses a qualitative approach based on document analysis. The primary data are drawn from a research report containing descriptions of JPH implementation, cost schemes, socialization practices, and quotations from field actors. The data were analyzed through thematic content analysis involving repeated reading, open coding, code grouping, and the identification of cross-theme patterns. The findings show that the halal label operates as a market-valued symbol that enhances reputation, competitiveness, and competitive pressure. Compliance also has a price because formal costs, additional costs, and the need for assistance can burden business actors, especially small enterprises. Acceleration through national targets and facilitation programs expands the adoption of certification, but implementation still faces friction arising from authority pluralism, regulatory changes, technological barriers, and uncertainty in the fatwa process. From a fiqh-legal perspective, halal certification gains dual legitimacy from state regulations and religious norms. However, this legitimacy must be balanced with a maslahah-based policy design so that certification does not become a mechanism of exclusion. This study contributes by showing that JPH is not merely an administrative instrument, but an arena of co-production among symbols, costs, authority, and market interests. Studi ini bertujuan menganalisis bagaimana Sistem Jaminan Produk Halal (JPH) di Indonesia mengubah halal dari norma konsumsi keagamaan menjadi infrastruktur pasar dan hukum. Analisis berfokus pada komodifikasi label, biaya kepatuhan, akselerasi kebijakan, dan ketegangan otoritas dalam implementasi JPH. Studi ini menggunakan pendekatan kualitatif berbasis analisis dokumen. Data utama berasal dari laporan penelitian yang memuat deskripsi implementasi JPH, skema biaya, praktik sosialisasi, dan kutipan aktor lapangan. Data dianalisis melalui analisis isi tematik melalui pembacaan berulang, pengodean terbuka, pengelompokan kode, dan identifikasi pola lintas tema. Temuan menunjukkan bahwa label halal bekerja sebagai simbol bernilai pasar yang meningkatkan reputasi, daya saing, dan tekanan kompetitif. Kepatuhan juga memiliki harga karena biaya formal, biaya tambahan, dan kebutuhan pendampingan dapat membebani pelaku usaha, khususnya usaha kecil. Akselerasi melalui target nasional dan program fasilitasi memperluas adopsi sertifikasi, tetapi implementasi masih menghadapi friksi akibat pluralisme otoritas, perubahan regulasi, hambatan teknologi, dan ketidakpastian proses fatwa. Dari perspektif fikih-hukum, sertifikasi halal memperoleh legitimasi ganda dari regulasi negara dan norma agama. Namun, legitimasi tersebut harus diimbangi dengan desain kebijakan berbasis maslahah agar sertifikasi tidak berubah menjadi mekanisme eksklusi. Studi ini berkontribusi dengan menunjukkan bahwa JPH tidak semata-mata merupakan instrumen administratif, melainkan juga arena ko-produksi antara simbol, biaya, otoritas, dan kepentingan pasar.